1956
DOI: 10.1161/01.res.4.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Blood (Fe 59 ) and Plasma (I 131 ) Volumes of Rats Determined by Liquid Nitrogen Freezing

Abstract: A standard method is described wliich gives reproducible blood volume values for rats and their various organs and tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
0
1

Year Published

1973
1973
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(126 citation statements)
references
References 0 publications
8
117
0
1
Order By: Relevance
“…Corrected v b (2.47 Ϯ 0.65%) agreed with other reports, especially those in rabbit tibialis anterior (2.1 Ϯ 0.7%) (14), the most similar to the muscle analyzed in our study. It is noteworthy that our v b agreed with those obtained using entirely different methods, such as a steady-state MRI (1.5 Ϯ 1.0%) (16) or autoradiography technique (2.29 Ϯ 0.28%) (17). Despite the use of corrected AIFs, our v b results may be slightly lower than the truth, due to potential effects of water exchange and since the true v b is known to be an upper bound on Patlak's estimate (18).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Corrected v b (2.47 Ϯ 0.65%) agreed with other reports, especially those in rabbit tibialis anterior (2.1 Ϯ 0.7%) (14), the most similar to the muscle analyzed in our study. It is noteworthy that our v b agreed with those obtained using entirely different methods, such as a steady-state MRI (1.5 Ϯ 1.0%) (16) or autoradiography technique (2.29 Ϯ 0.28%) (17). Despite the use of corrected AIFs, our v b results may be slightly lower than the truth, due to potential effects of water exchange and since the true v b is known to be an upper bound on Patlak's estimate (18).…”
Section: Discussionsupporting
confidence: 83%
“…Agreement was found, particularly with AIFs derived from corrected preinjection blood T 1 . Figure 5 compares this study to literature values for muscle (14,16,17). Better agreement was obtained for parameters derived from corrected AIFs.…”
Section: Mri Data Analysismentioning
confidence: 54%
“…The 2-phosphate of 2,3-diphosphoglycerate (2,3DPG) has a chemical shift in the same region as Pi [30] and it has been suggested that it contributes to signal in this region [ 131. The concentration of 2,3-DPC in the erythrocytes of the rat is -7 mM [3 l] and the brain blood volume is -3% [32]. Assuming a haematocrit of 40% and a uniform distribution of blood throughout the brain, the concentration of 2,3DPC which we would detect by NMR would be <5% of the mean estimated Pi concentration.…”
Section: Discussionmentioning
confidence: 97%
“…4 ml 100 g -1, while Shockley and LaManna (1988), using transit time measurements, measured a whole brain CBV of 3.4 ml 100 g -1. Everett et al (1956) killed rats by immersion in liquid N2 and obtained values of 3.0 ml 100 g-l.…”
Section: Discussionmentioning
confidence: 99%